X‐ray and UV photoelectron spectroscopy of Ag nanoclusters. (3rd April 2020) - Bolli, Eleonora; Mezzi, Alessio; Burratti, Luca; Prosposito, Paolo; Casciardi, Stefano; Kaciulis, Saulius
Abstract : The main purpose of the present work is to analyze a series of Ag nanoparticles (NPs) with different size or ligand functionalization by using X‐ray photoelectron spectroscopy (XPS) and to identify the differences in the band‐shape and energy peak position of photoemission spectra due to the particle dimension. A transmission electron microscopy characterization was performed, to verify the consistency of the results. Three types of samples were prepared starting from AgNO3 water solution and adding different capping agents. In the first two cases, the formation of NPs was promoted by the reduction of silver ions Ag +1 to metallic Ag 0 through the addition of sodium borohydride, whereas in the last case, it was triggered by the exposure to UV light. Depending on the size of the NPs, a different physical behavior can be recognized. NPs with diameter of about 5 nm are characterized by the phenomenon of localized surface plasmon resonance (LSPR). The other type of samples having a diameter of about 1.5 nm presents discrete energy levels instead of electronic bands, and in this case, a typical fluorescence phenomenon can be observed. In the latter case, we can refer to such systems as nanoclusters. The XPS analyses were focused on the Ag 3D spectra looking for the possible shifts of the Ag doublet as a function of the particles size. The ultraviolet photoelectron spectroscopy with He II source was used for the investigation of possible changes in the valence band.